Analysis on Large Deformation Compensation Method for Grinding Machine - Wang Ya-jie; Huang Yun; Zhang Die; Zhu Deng-wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The positioning accuracy of computer numerical control machines tools and manufacturing systems is affected by structural deformations, especially for large sized systems. Structural deformations of the machine body are difficult to model and to predict. Researchs for the direct measurement of the amount of deformation and its compensation are farly limited in domestic and overseas,not involved to calculate the amount of deformation compensation. A new method to compensate large deformation caused by self-weight was presented in the paper. First of all, the compensation method is summarized; Then,static force analysis was taken on the large grinding machine through APDL(ANSYS Parameter Design Language). It could automatic extract results and form data files, getting the N points displacement in the working stroke of mechanical arm. Then, the mathematical model and corresponding flat rectangular function were established. The conclusion that the new compensation method is feasible was obtained through the analysis of displacement of N points. Finally, the MATLAB as a tool is used to calculate compensate amount and the accuracy of the proposed method is proved. Practice shows that the error caused by large deformatiion compensation method can meet the requirements of grinding. DOI: http://dx.doi.org/10.11591/telkomnika.v11i8.3132